Strategies for urban development in Leipzig, Germany : harmonizing planning and equity - Garcia-Zamor, Jean-Claude (Public Administration, Governance and Globalization, 2014)
The demographic pressure caused by migration offers a considerable challenge for urban centers today. It results in an uneven development of the community and focus of urban planners becomes how to provide decent, low-cost housing and transportation in order to facilitate the integration of poorer residents among the rest of the community. In large industrialized countries the challenges of urban policy-makers are made even more complicated since these governments depend on state or federal legislators to obtain the massive amounts of funding required for adequately addressing these local issues that are in global cause. The book analyzes the strategies for urban development in Leipzig, Germany, and shows how civic leaders were able to harmonize planning and equity. They relied heavily on two interesting approaches in that process: the promotion of culture as a key component of urban development and the reconciliation of the inevitable process of gentrification with social equity. The book also looks at the globalization aspect of urban development, reviews research in social equity in urban development in Europe and the United States and describes sustainability as an important element of urban renaissance.